Pemanfaatan Internet Untuk Penelitian Dan Dampaknya Terhadap Penelitian Pariwisata Dan Hospitality - Yukiko Hiro Mantu (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2020)
ABSTRACT Rapid development of internet technology can influence the way we do research. Yet there are some weaknesses of research by using internet such as anonymity, demography of respondent, accessibility, risk of plagiarism, and reliability, the benefit is obvious. Academic staffs, researchers or students are advantaged since they can use it for referencing tool, on-line database, mailing list and media for sampling dissemination. Indeed, this paper discuss the implication of internet development on tourism & hospitality research since there are a lot of tourism & hospitality related resources in the web that can be found easily by using on-line database or search engine. Keywords: Tourism & Hospitality research, Internet, Elektronic Journal, Online Database, Online Research